NGOs, Foreign Aid, and Development in Nepal - Karkee, Rajendra; Comfort, Jude (Frontiers in Public Health, 2016)
The number of non-governmental organizations (NGOs) working in Nepal has grown significantly since the 1990s due to a range of factors. A total of 39,759 NGOs and 189 international non-governmental organizations were registered in Nepal between 1977 and 2014 in various sectors, including health, agriculture, poverty alleviation, and good governance. Despite thousands of NGOs and significant amounts of foreign aid, Nepal remains one of the poorest countries in South Asia. The case of Nepal indicates that aid and donor support alone are insufficient for sustained development.